GSTZ1 Expression and Chloride Concentrations Modulate Sensitivity of Cancer Cells to Dichloroacetate - Jahn, Stephan C. (Biochim Biophys Acta, 2016)
Dichloroacetate (DCA), commonly used to treat metabolic disorders, is under investigation as an anti-cancer therapy due to its ability to reverse the Warburg effect and induce apoptosis in tumor cells. While DCA’s mechanism of action is well-studied, other factors that influence its potential as a cancer treatment have not been thoroughly investigated. Here we show that expression of glutathione transferase zeta 1 (GSTZ1), the enzyme responsible for conversion of DCA to its inactive metabolite, glyoxylate, is downregulated in liver cancer and upregulated in some breast cancers, leading to abnormal expression of the protein. The cellular concentration of chloride, an ion that influences the stability of GSTZ1 in the presence of DCA, was also found to be abnormal in tumors, with consistently higher concentrations in hepatocellular carcinoma than in surrounding non-tumor tissue. Finally, results from experiments employing two- and three-dimensional cultures of HepG2 cells, parental and transduced to express GSTZ1, demonstrate that high levels of GSTZ1 expression confers resistance to the effect of high concentrations of DCA on cell viability. These results may have important clinical implications in determining intratumoral metabolism of DCA and, consequently, appropriate oral dosing.